ANALYSIS OF ANDROID-BASED E-LIBRARY USER SATISFACTION AT GALUH UNIVERSITY LIBRARY USING TAM AND EUCS - Septian, Luffi; Alijoyo, Antonius; Herman, Maman (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
E-Library is a library that manages and stores library collections in the form of books, journals, articles, theses, theses and other documents in digital format. so that in the process of searching for information, users can easily search and access collections online. E-Library has been adopted by several platforms, including Android devices. Galuh University Library is one of the universities that has provided Android-based E-Library services, but in its utilization it is necessary to analyze the acceptance and level of satisfaction of users of the application. This study aims to analyze the acceptance and level of satisfaction of E-Library users at Galuh University. This study uses a quantitative approach to analyze user satisfaction with Android-based E-Library at Galuh University Library. This study integrates the Technology Acceptance Model (TAM) and End-User Computing Satisfaction (EUCS) as the main framework and involves 138 respondents as samples. The results of the study revealed that 'Perceived Usefulness', 'Content', 'Accuracy', and 'Timeliness' have a significant positive influence on user attitudes, which in turn have an impact on their satisfaction with E-Library. The relationship between user attitude and user satisfaction was confirmed to be strong, indicating that a positive attitude towards the E-Library system contributes to a higher level of satisfaction. Meanwhile, 'Perceived Ease of Use' and 'Format' did not show a significant effect, indicating that other factors play a greater role in shaping user attitudes. This study is limited because it did not consider external variables such as gender and user experience, which are recommended for further research. These results provide important insights for the development of a more effective E-Library, by emphasizing aspects that contribute to increasing user satisfaction.